2020
DOI: 10.3390/ijerph17239073
|View full text |Cite
|
Sign up to set email alerts
|

The Bittersweet Effects of COVID-19 on Mental Health: Results of an Online Survey among a Sample of the Dutch Population Five Weeks after Relaxation of Lockdown Restrictions

Abstract: Previous research shows that crises can have both negative and positive mental health effects on the population. The current study explored these effects in the context of the COVID-19 pandemic after relaxation of governmental measures. An online survey was administered among a representative sample of the Dutch population (n = 1519) in June 2020, ten weeks after the peak of COVID-19 had passed, and five weeks after restrictions were relaxed. Participants were asked about mental health, adverse events during C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 37 publications
1
26
4
Order By: Relevance
“…In contrast to our findings, some studies found that the lifting of the lockdown had no significant impact on mental health [ 38 , 39 ]. Richter and colleagues recently reviewed the literature on mental health problems in general (and not only clinical) populations of several countries during and after the first lockdown [ 23 ].…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to our findings, some studies found that the lifting of the lockdown had no significant impact on mental health [ 38 , 39 ]. Richter and colleagues recently reviewed the literature on mental health problems in general (and not only clinical) populations of several countries during and after the first lockdown [ 23 ].…”
Section: Discussioncontrasting
confidence: 99%
“…A large number of studies support that the conclusion that the novel coronavirus (SARS-CoV-2) and its corresponding disease (COVID- 19) have dramatically impacted people's mental health and behavior [1][2][3][4][5], with very few studies suggesting otherwise [6]. Mental health hotlines in the United States experienced 1,000% increases during the month of April, when most people were under lockdown because of the pandemic [7].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the explained variance of both investigated models (10.3% and 9.0%) was quite high considering the large scale of other factors that might contribute to worrying or loneliness, like dealing with uncertainty, 46 having diminished social contacts in times of crisis, e.g., the COVID-19 lockdown, 47 and unfamiliarity with digital tools for staying connected with the person with dementia. 48 …”
Section: Discussion/ Conclusionmentioning
confidence: 99%